IMPACT OF MOTOR DEVELOPMENT IN CHILDREN WITH CEREBRAL PALSY ON THE QUALITY OF LIFE AND GENERAL HEALTH STATUS OF CAREGIVERS (2011)
Cerebral Palsy (CP) is a neuropaediatric condition which occurs as a result of damage to an immature brain resulting in abnormal motor development requiring special care. Caring for children with CP may affect the quality of life and/or impact on the general health status of their caregivers. There is paucity of longitudinal studies exploring this inter-relationship. The relationship between motor development of Children With Cerebral Palsy (CWCP) and impact of caring on each of Quality of Life (QoL) and General Health Status (GHS) of caregivers of CWCP was therefore evaluated. Participants in this longitudinal study comprised of consecutively recruited 107 CWCP and 107 Caregivers of CWCP (CCWCP) from four specialist hospitals in southwest Nigeria. Ninety eight caregivers of normally developing children were also recruited to constitute the Control Group (CG). The CCWCP and CG were matched for age and socio-economic status. However 67 participants in each of the CWCP, CCWCP, and 87 in the CG completed the study. Gross motor function of the CWCP was assessed in the clinic and their respective homes using the Gross Motor Function Measure (GMFM)(scored 0 to 100) at baseline and monthly for eight consecutive months in order to assess the likely influence of the home and the clinic environments on their motor function. The QoL and GHS of the CCWCP and CG participants were assessed at baseline and for eight consecutive months using the World Health Organization Quality of Life Questionnaire (WHOQoL) (scored 1 to 5) and General Health Questionnaire (GHQ)(scored 0 to 3) respectively. Data were analyzed using descriptive statistics, Wilcoxon Signed Rank, Friedman's ANOVA, Spearman's Correlation and Mann-Whitney U at p = 0.05. At baseline, the CCWCP had a significantly lower median WHOQoL score of 84.0 (range 48.0-115.0) than their CG counterparts (median 96.0, range 62.0-123.0). CCWCP also recorded a significantly higher median GHQ score of 16.0 (range 4.0'48.0) than the controls (median 9.0, range 1.0-22.0) indicating lower QoL and GHS. At the 8th month, the CG had significantly higher WHOQoL scores (median 96.0, range 63.0-124.0 vs median 89.0, range 60.0-118.0). Among the CWCP, baseline GMFM score was higher at home (median 15.7, range 0-71.9) than in the clinic (median 13.6, range 0-71.9). Similarly the home GMFM scores were significantly higher at the 8th month (median 28.9, range 0-100.0) than in the clinic (median 25.8, range 0-100.0). The GMFM score increased significantly between baseline and 1st; 3rd and 4th; 5th and 6th; and 7th and 8th months. The GMFM scores had significant positive correlation with WHOQoL scores at the 5th (r = 0.3), 7th (r =0.4) and 8th months (r =0.4). The better the motor development in children with cerebral palsy, the higher the quality of life and general health status of caregivers. Performance of motor function was better at home compared to the clinic suggesting that home environment should be simulated during management of children with cerebral palsy.